The contemporary perspective of nomadism in the trajectory of a black teacher (Revista Apotheke, 2022)
Understanding nomadism in a decolonized perspective is to awaken new perceptions for contemporaneity. However, this research aims to describe the trajectory of nomadism of the narrator of the present research, appropriating a family, social, ethnic, racial, educational and professional context. The theoretical framework included discussions about nomadism, racial ethnic relations, black feminism. The methodological procedures adopted consisted of an autobiographical research which was chosen as a research instrument the narratives and memories of the narrator. The data obtained reflect the theoretical foundation, where the presence of issues related to nomadism, black feminism, and ethnic relations was noticed. Based on the results and discussions presented, it is considered the importance of bringing the concept of nomadism to the contemporary world with the intention of the subjects being perceived in this process of movement/displacements and changes in society as an act of liberation.
Keywords: Nomadism; Black Feminism; Ethnic Racial Relations